Can Playfulness be Stimulated? A Randomised Placebo‐Controlled Online Playfulness Intervention Study on Effects on Trait Playfulness, Well‐Being, and Depression. Issue 1 (25th August 2020) - Proyer, René T.; Gander, Fabian; Brauer, Kay; Chick, Garry
Abstract : Background: While there are numerous applications of play‐based interventions, there is little research on playfulness‐based interventions. We applied interventions that aim at stimulating playfulness and test effects on happiness and depressive symptoms. Method: In a randomised placebo‐controlled online intervention, N  = 533 participants were assigned to one of three 1‐week playfulness conditions (i.e. three playful things, using playfulness in a new way, and counting playfulness) or a placebo condition. Participants reported on global playfulness, facets of playfulness, well‐being, and depression at pretest, posttest, and at follow‐ups after 2, 4, and 12 weeks. Results: All interventions increased expressions in all facets of playfulness, had short‐term effects on well‐being, and ameliorated depression. Conclusion: Overall, findings suggest that playfulness can be stimulated by short self‐administered interventions.